Kommentar zu Anne Lise Marstrand-Jørgensen: Tochter des Lichts. Ein Hildegard von Bingen-Roman. Berlin 2012 - Mersch, Katharina Ulrike (Die Kunde: Zeitschrift für niedersächsische Archäologie)

Scalability, Elasticity, and Efficiency in Cloud Computing - Lehrig, Sebastian; Eikerling, Hendrik; Becker, Steffen (Proceedings of the 11th International ACM SIGSOFT Conference on Quality of Software Architectures)

Carry-over coarticulation in joint angles - Hansen, Eva; Grimme, Britta; Reimann, Hendrik; Schöner, Gregor (Experimental brain research)

Unravelling the Tangled Threads of Ancient Embroidery - A Compilation of Written Sources and Archaeologically Preserved Textiles (mit A. Paetz gen. Schieck) - Droß-Krüpe, Kerstin (Greek and Roman Textiles and Dress - An Interdisciplinary Anthology,)

Textile Tools in Papyri From Imperial Egypt - Droß-Krüpe, Kerstin (Textiles, Tools and Techniques of the 1st Millennium AD from Egypt and Neighbouring Countries. Proceedings of the 8th Textiles from the Nile Valley Conference, Antwerp, October 2013)

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 4 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Gewalt und Zuchtmittel in der Schulgeschichte - Freitag, Christine (Handbuch Aggression, Gewalt und Kriminalität bei Kindern und Jugendlichen)

Good retest reliability of the rate of speech errors evoked by 10 Hz navigated repetitive transcranial magnetic stimulation in healthy volunteers: German Medical Science GMS Publishing House - Pieczewski, Julia; Neuschmelting, Volker; Thiele, Kristina; Grefkes, Christian; Goldbrunner, Roland; Weiss Lucas, Carolin
Keywords: 610 Medical sciences; Medicine; reliability; speech mapping; TMS

Children’s syntactic-priming magnitude: lexical factors and participant characteristics - Foltz, Anouschka; Thiele, Kristina; Kahsnitz, Dunja; Stenneken, Prisca (Journal of child language)
This study examines whether lexical repetition, syntactic skills, and working memory (WM) affect children’s syntactic-priming behavior, i.e. their tendency to adopt previously encountered syntactic structures. Children with Specific Language Impairment (SLI) and typically developing (TD) children were primed with prenominal (e.g., the yellow cup) or relative clause (RC; e.g., the cup that is yellow) structures with or without lexical overlap and performed additional tests of productive syntactic skills and WM capacity. Results revealed a reliable syntactic-priming effect without lexical boost in both groups: SLI and TD children produced more RCs following RC primes than following prenominal primes. Grammaticality requirements influenced RC productions in that SLI children produced fewer grammatical RCs than TD children. Of the additional measures, WM positively affected how frequently children produced dispreferred RC structures, but productive syntactic skills had no effect. The results support an implicit-learning account of syntactic priming and emphasize the importance of WM in syntactic priming tasks.
Keywords: Child; Female; Germany; Humans; Linguistics; Male; Memory; Short-Term; Vocabulary

Lexical alignment in triadic communication - Foltz, Anouschka; Gaspers, Judith; Thiele, Kristina; Stenneken, Prisca; Cimiano, Philipp (Frontiers in Psychology)
Lexical alignment refers to the adoption of one’s interlocutor’s lexical items. Accounts of the mechanisms underlying such lexical alignment differ (among other aspects) in the role assigned to addressee-centered behavior. In this study, we used a triadic communicative situation to test which factors may modulate the extent to which participants’ lexical alignment reflects addressee-centered behavior. Pairs of naïve participants played a picture matching game and received information about the order in which pictures were to be matched from a voice over headphones. On critical trials, participants did or did not hear a name for the picture to be matched next over headphones. Importantly, when the voice over headphones provided a name, it did not match the name that the interlocutor had previously used to describe the object. Participants overwhelmingly used the word that the voice over headphones provided. This result points to non-addressee-centered behavior and is discussed in terms of disrupting alignment with the interlocutor as well as in terms of establishing alignment with the voice over headphones. In addition, the type of picture (line drawing vs. tangram shape) independently modulated lexical alignment, such that participants showed more lexical alignment to their interlocutor for (more ambiguous) tangram shapes compared to line drawings. Overall, the results point to a rather large role for non-addressee-centered behavior during lexical alignment.

P156. Good long-term error rate retest reliability of 10Hz neuronavigated repetitive TMS speech/language mapping in healthy volunteers - Pieczewski, J.; Neuschmelting, V.; Nettekoven, C.; Thiele, Kristina; Reck, N.; Goldbrunner, R.; Grefkes, C.; Lucas, C. Weiß (Clinical Neurophysiology)

Temporal Effects of Alignment in Text-Based, Task-Oriented Discourse - Foltz, Anouschka; Gaspers, Judith; Meyer, Carolin; Thiele, Kristina; Cimiano, Philipp; Stenneken, Prisca (Discourse Processes)

Kontrastive Linguistik und Fremdsprachendidaktik Iberoromanisch ‒ Deutsch. Studien zu Morphosyntax, Mediensprache, Lexikographie und Mehrsprachigkeitsdidaktik (Spanisch, Portugiesisch, Katalanisch, Deutsch) - Bürgel, Christoph (Zeitschrift für romanische Sprachen und ihre Didaktik)

20 Jahre Lernen mit dem World Wide Web - Technik und Bildung im Dialog - Keil, Reinhard; Harald, Selke

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Brücken bauen in der Werkstatt: Die Bedeutung von Forschungswerkstätten in der Bearbeitung des Theorie-Praxis-Verhältnisses in der Lehrer/innenbildung - Thünemann, Silvia; Freitag, Christine (Brücken bauen – Praxisforschung zu Übergängen im Bildungssystem)

Feministische Kapitalismuskritik - Riegraf, Birgitt; Aulenbacher, Brigitte; Völker, Susanne
Welche Herrschaftsverhältnisse liegen dem Gegenwartskapitalismus zugrunde? Wie prägen sie seine Entwicklung? Welche Veränderungen lassen sich feststellen? Diesen Fragen geht der Einstiege-Band aus einer dezidiert feministischen Perspektive nach: Für ihre Antworten legen die Autorinnen intersektionelle und kapitalismustheoretische, anerkennungs- und gerechtigkeitstheoretische, praxistheoretische und poststrukturalistische Perspektiven an. Wie sich Herrschaft im Geschlechterverhältnis ausdrückt und wandelt, zeigen sie anhand feministischer Erkenntnisse zur Prekarisierung, zur Subjektivierung, zur Entgrenzung von Arbeit und zum Wandel des Sozialstaats, aber auch zur finanzökonomischen Entwicklung und zu globalen Versorgungsketten. Dabei loten sie Ansätze der Subaltern Studies, des Ecofeminism und des Material Feminism in ihrer Reichweite für die feministische Gesellschaftsanalyse und Kapitalismuskritik aus. Das Buch ist für die Lehre geeignet und für gesellschaftspolitisch Interessierte auch außerhalb der Wissenschaft informativ.
Keywords: Feminismus Kapitalismus Kritik

Faithful Realizability of Tropical Curves - Cheung, Man-Wai; Fantini, Lorenzo; Park, Jennifer; Ulirsch, Martin (International Mathematics Research Notices)

Tropical compactification in log-regular varieties - Ulirsch, Martin (Mathematische Zeitschrift)